(untitled) - Manas Mukul Mandal; Rohit Shaw; Narendranath Mukhopadhyay; Sumon Kumar Saha (Asian Journal of Medical Research, 2020)
Fetus in fetu is a very unusual pathology in which a deformed underdeveloped fetus is found inside the body of another child. It is an uncommon abnormality and thought to be a result of abnormal embryogenesis in the case of diamniotic monochorionic pregnancy. Most commonly presents as a palpable mass in the abdomen. Imaging modalities can reveal the presence of bony elements within the mass cavity like vertebral bodies, long bones, and even underdeveloped organ systems. It should be differentiated from mature or well-organized teratoma & other causes of infantile abdominal masses like Nephroblastoma, Neuroblastoma, Hydronephrosis & malignant germ cell tumors in undescended testis. Surgery is the mainstay of treatment. To date around two hundred cases have been reported worldwide.